Bureaucratic Reform and Relational Bias in the Transfer of Civil Servants: Evidence from Timor Tengah Selatan Regency, East Nusa Tenggara - Otniel Elisman Tulle; Hotlif Arkilaus Nope; Dhessy Arisandielis Kase; I Putu Yoga Pradana (Catalist Indo Publisher, 2026)
Background Bureaucratic reform in Indonesia positions the merit system as a fundamental principle in the management of the State Civil Apparatus (ASN) in order to achieve a professional, neutral, and service-oriented bureaucracy. However, its implementation at the local level continues to face substantial challenges, particularly due to political intervention and relational bias. This study aims to examine the distortion of the merit system in civil servant transfers in Timor Tengah Selatan Regency, East Nusa Tenggara Province, and to identify the dominant forms of relational bias and their implications for bureaucratic performance and public service delivery. Methods This study adopts a qualitative approach using a case study design. Six informants were purposively selected, comprising civil servants who had experienced job transfers as well as individuals with in-depth knowledge of local bureaucratic and political dynamics. Data were collected through in-depth interviews, non-participant observation, and document analysis, and were analyzed using data reduction, data display, and conclusion-drawing techniques supported by triangulation. Results The findings reveal that civil servant transfers in Timor Tengah Selatan Regency are not fully based on considerations of competence and performance, but are strongly influenced by post-election political interests, personal proximity, kinship ties, and patronage. The role of the Position and Rank Consideration Board (Baperjakat) tends to be largely administrative and has not functioned effectively as an objective decision-making mechanism. Non-merit-based transfers have adversely affected civil servant motivation, weakened professional work culture, and potentially diminished the quality of public services. Conclusions This study concludes that the failure to implement the merit system is not merely attributable to regulatory weaknesses, but primarily to the lack of political will to uphold civil servant neutrality and professionalism. Accordingly, strengthening oversight mechanisms, enforcing strict sanctions, and transforming local political culture are essential to ensure the effective implementation of bureaucratic reform at the regional level.